2020
DOI: 10.3748/wjg.v26.i33.4983
|View full text |Cite
|
Sign up to set email alerts
|

Acute liver failure and death predictors in patients with dengue-induced severe hepatitis

Abstract: BACKGROUND Liver injury in patients with dengue infection is common. Most patients have mild and transient hepatitis. Acute liver failure (ALF) in dengue infection is rare but results in an extremely poor prognosis. AIM To identify prognostic predictors of ALF and death in patients with dengue-induced severe hepatitis (DISH). METHODS We retrospectively reviewed 2311 serologically confirmed adolescent and adult dengue patients who were hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
1
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 34 publications
3
21
1
2
Order By: Relevance
“…The mortality rate of ALF was 10 of 17 SDD patients (58.82%). They concluded that the MELD score is the best predictor of ALF in dengue-induced severe hepatitis (DISH) patients[ 46 ].…”
Section: Dhf and Acute Liver Failurementioning
confidence: 99%
“…The mortality rate of ALF was 10 of 17 SDD patients (58.82%). They concluded that the MELD score is the best predictor of ALF in dengue-induced severe hepatitis (DISH) patients[ 46 ].…”
Section: Dhf and Acute Liver Failurementioning
confidence: 99%
“…AKI in dengue patients may recover on its own, but may also require kidney replacement therapy [ 7 , 20 ]. Liver function damage is relatively common in dengue patients and can lead to acute liver failure [ 6 , 10 ]. Disorders of coagulation parameters such as APTT, PT, fibrinogen are common in patients with severe dengue [ 12 ], leading to severe bleeding, especially in prolonged shock [ 2 , 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…This was either a result of direct viral toxicity or compromised immune response to the virus [ 25 ]. Although the bilirubin parameter was rarely suggested, however some studies have also recognized that bilirubin may be associated with severe dengue prognosis [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations